The new Penguin dictionary of science - "Clugston, M.J" (Penguin Books, London, 1998)
"Chemistry, physics, mathematics, molecular biology, biochemistry, human anatomy, astronomy, computing: all these topics are covered in this dictionary. With clear and up-to-date definitions of some 7,000 scientific terms, backed by scores of illustrations and diagrams, The New Penguin Dictionary of Science forms the ideal reference tool for student, researcher and enthusiastic layperson alike."--Jacket